PENGARUH SINISME ORGANISASI TERHADAP KINERJA KARYAWAN: PERAN MOTIVASI INTRINSIK SEBAGAI VARIABEL MEDIASI - Risgiyanti Risgiyanti (Neraca, 2016)
Organizational cynicism was currently an important topic in the academic community as well as business but the related research was relatively neglected. Several researches that had tested the impact of organizational cynicism still showed different results. This research tested the impact of organizational cynicism especially affective cynicism about the performance by using intrinsic motivation as mediating variabel. The data were taken from manager and employee of 23 BTM Primer member of Pusat KJK Syariah BTM Jawa Tengah. The sample of this research were 161 respondents. This research was using survey method with quantitative approach. The tool of analysis used in the study wasPartial Least Square (PLS) which used WarpPLS 3.0 program. The result showed that affective cynicism directly affected the employee performance. But intrinsic motivation had no mediating role between affective cynicism and employee performance. This study opens new avenues for research on organizational cynicism and carries implications for theory and practice affective cynicism